2014
DOI: 10.1002/2014jd021922
|View full text |Cite
|
Sign up to set email alerts
|

Automated decision algorithm applied to a field experiment with multiple research objectives: The DC3 campaign

Abstract: Automated decision systems have shown the potential to increase data yields from field experiments in atmospheric science. The present paper describes the construction and performance of a flight decision system designed for a case in which investigators pursued multiple, potentially competing objectives. The Deep Convective Clouds and Chemistry (DC3) campaign in 2012 sought in situ airborne measurements of isolated deep convection in three study regions: northeast Colorado, north Alabama, and a larger region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Being tested during DC3 field operations were probabilistic forecasts and automated decision algorithms to aid in field campaign decisions. Hanlon, Small, et al () found that automated decision algorithms would have increased the yield of data from the field campaign, while Hanlon, Young, et al () showed that their probabilistic forecasts had predictive skill over climatology for each of the DC3 regions. Another pivotal reason for the success of DC3 was the strong cooperation and interaction between the lead PIs for the project.…”
Section: Discussionmentioning
confidence: 99%
“…Being tested during DC3 field operations were probabilistic forecasts and automated decision algorithms to aid in field campaign decisions. Hanlon, Small, et al () found that automated decision algorithms would have increased the yield of data from the field campaign, while Hanlon, Young, et al () showed that their probabilistic forecasts had predictive skill over climatology for each of the DC3 regions. Another pivotal reason for the success of DC3 was the strong cooperation and interaction between the lead PIs for the project.…”
Section: Discussionmentioning
confidence: 99%